Measuring and Improving Stakeholder Welfare Is Easier Said than Done - Gurun, Umit G.; Nickerson, Jordan; Solomon, David H. (Journal of Financial and Quantitative Analysis, 2023)
While corporate social responsibility by firms aims at improving welfare for different social groups, whether it achieves this is often difficult to measure. After Apr. 2018 protests, Starbucks enacted policies that anybody could sit in their stores and use the bathroom without making a purchase. Using anonymized cellphone location data, we estimate this led to a 7.0% decline in attendance relative to other nearby coffee shops. The effect is 84% larger near homeless shelters and larger for Starbucks’ wealthier customers. The average time spent per visit declined by 4.1%. Public urination citations decreased near Starbucks locations, but other minor crimes were unchanged.